A Bibliometric Article Regarding Twin Technology In Technology Management For The Year 2019-2025: Industry In Malaysia - Mazzlida Mat Deli; Ummu Ajirah Abdul Rauf; Maryam Jamilah Asha’ari; Ainul Huda Jamil; Astri Ayu Purwati; Siti Intan Nurdiana Wong Abdullah; Fauziah Ismail (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
The purpose of this research is to analyze the application of digital twin technology in the efficient management of new innovative technology. The research is directed to perform a bibliometric analysis of the subject topic. The relevancy of the research can be underlined by the fact that digital twin technologies are a popular concept of Industry 4.0. In addition, this research is advantageous to identify the application of digital twin technology in efficient technology management, especially in Malaysia. As a scope, it would highlight possible use cases of digital twin technology. The review of existing literature highlighted that digital twin technology has serious use case potential in supply chain operations. Whereas other scholars argue that digital twin technology can bring out major disruptive innovations to improve the internal competencies of major manufacturing firms. The methodology for the research involves the use of secondary data with bibliometric analysis. It has been identified in the findings that there is a rise in research associated with digital twin technology between the timelines from 2019 to 2022. Furthermore, Chinese Academies are most active in propagating research on variables like digital twins.